THE POTENTIAL FOR DEVELOPING EDUTOURISM ON POST GOLD MINE LAND IN PALALUAR NAGARI BASED ON SUSTAINABLE AGRICULTURE - Dara Latifa; Salvia; Yummama Karmaita; Dedeh Kurniasih; Resa Yulita (RADJA PUBLIKA, 2023)
The change in behavior from miners back to farmers requires the people of Palaluar Nagari to reclaim their land, which is generally a former gold mine. However, natural land reclamation takes quite a long time and costs a lot of money so it needs support from various parties, especially the government. Government of Palaluar Nagari, in order to improve land to achieve food security, launched a program based on sustainable agriculture. Sustainable tourism development by utilizing local resources does not only focus on environmental aspects but also economic and social aspects of the community. The implementation of land reclamation is carried out by developing educational tourism which involves tourists in reclaiming land, which includes two edutourism packages, namely the Sitampan Edutourism Package and the Sikamek Edutourism Package which are based on an integrated farming system and are a form of sustainable tourism. The research aims to examine the potential for developing sustainable agriculture-based education tourism in Palaluar Nagari using descriptive methods. The development of educational tourism on reclaimed land from a former gold mine in Nagari Palaluar based on sustainable agriculture has development potential because it provides positive impacts from social, economic and environmental aspects.